Life on the edge: the plankton and chemistry of Beaver Lake, an ultra-oligotrophic epishelf lake, Antarctica - J Laybourn-Parry; Wendy Quayle; T Henshaw; A Ruddell; HJ Marchant (2001)
Life on the edge: the plankton and chemistry of Beaver Lake, an ultra-oligotrophic epishelf lake, Antarctica